Treatment of Gonorrhea by Acupuncture plus Drugs： A Case of Report - 王省 张西安 (Journal of acupuncture and tuina science, 2005)
Gonorrhea is a sexually transmitted diseases caused by bacteria called Neisseria gonorrhoeae. The bacteria can be passed from one person to another through sexual intercourse, and one can also catch gonorrhea from the infected clothing, bed-sheet and quilt cover. It often can be treated with antibiotics in modern medicine and drugs of clearing away heat and toxic material in Chinese medicine. The authors adopted acupuncture and moxibustion combined with oral administration of western medicine Ciprofloxacin and Chinese herbs Longdan Xiegan Wan （Pill of Gentiana for purging the liver fire） to cure a case of gonorrhea, now it is reported as fol Iows.